Exploring Trends in Teaching Stylistic Analysis: Syntactical Features in Selected British Fashion Magazine “Harper’s Bazaar” - Natassa Putri; Rugaiyah Rugaiyah (Utamax : Journal of Ultimate Research and Trends in Education, 2021)
Teaching English Stylistic to language students in Universitas Islam Riau has always been part of language or foreign language education. It is a study of linguistics about how someone expresses his or her ideas depend on the purpose of it. An advertisement is good example to study to see how the advertisers use a language to persuade the readers to buy their product or use their service. This research attempted to know the style of language on advertisement, namely syntactical feature in stylistic teaching-learning frameworks. This research used descriptive qualitative as the research design and textual analysis was used to analyse the data. There were 28 data from two editions of Harper’s Bazaar UK magazine. Based on the data obtained, it is found that there were 46 long-noun phrases, 16 short sentences in the form of present tense, 13 imperative and ellipsis, 3 incomplete sentences and association, 1 for simple and colloquial, ambiguity, syntactic parallelism. Students are required to have literary competence as they are exposed to extracts from literary works while studying English.